Phenolic composition and antioxidant capacity of cultivated artichoke, Madeira cardoon and artichoke‐based dietary supplements - Gouveia, Sandra C. (2021)
Cynara cardunculus var. scolymus (artichoke) and Cynara cardunculus var. ferocissima (Madeira cardoon) are two Asteraceae plants used in Madeira Archipelago in diet and also for medicinal issues. The present work aimed to compare the phenolic composition and quantify the main compounds of these two plants and two artichoke based dietary supplements (juice and dragées). The methanolic extract of the endemic plant cardoon was basi cally composed of caffeoylquinic acid isomers. The same compounds were observed in artichoke extract, where there was a larger number and variety of other phenolic compounds. Variations in qualitative and quantitative composition of the three artichoke based products were extensive, with only 3 components being common to all 3 products. Mono-O-diglycosilated flavonoids (luteolin, apigenin and quercetin) were found in the artichoke products but not in Madeira cardoon. 1,3-O-dicaffeoylquinic acid (cynarin), usually considered mainly responsi ble for the biological properties of artichoke, was found in high amounts ranging in most samples but was not detected in the analyzed commercial dragées. The antioxidant assays results reflected the highly diversified com position of the artichoke-based products, showing a high radical scavenger and reducing capacities, while the ex tract from Madeira cardoon was a poor antioxidant